Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1158/2159-8290.cd-13-0172
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Signaling Regulates DNA Repair in Prostate Cancers

Abstract: We demonstrate that the androgen receptor (AR) regulates a transcriptional program of DNA repair genes that promotes prostate cancer radioresistance, providing a potential mechanism by which androgen deprivation therapy (ADT) synergizes with ionizing radiation (IR). Using a model of castration-resistant prostate cancer, we show that second-generation antiandrogen therapy results in downregulation of DNA repair genes. Next, we demonstrate that primary prostate cancers display a significant spectrum of AR transc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
435
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 460 publications
(496 citation statements)
references
References 27 publications
14
435
5
1
Order By: Relevance
“…The majority of these studies have been conducted on prostate cancer cell lines and considerable effort has been made in defining AR targets in tumour epithelium [12][13][14][15][16][17]. This has revealed a transcriptional role for AR in tumour cells regulating cell proliferation, metabolism, survival and DNA repair [18,19]. Prostate cancer cell lines have also been used to determine the changes in AR transcriptional networks in both a hormonenaïve-and castrate-resistant setting and numerous studies have revealed distinct binding profiles in the androgen-independent setting [13,17,18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have been conducted on prostate cancer cell lines and considerable effort has been made in defining AR targets in tumour epithelium [12][13][14][15][16][17]. This has revealed a transcriptional role for AR in tumour cells regulating cell proliferation, metabolism, survival and DNA repair [18,19]. Prostate cancer cell lines have also been used to determine the changes in AR transcriptional networks in both a hormonenaïve-and castrate-resistant setting and numerous studies have revealed distinct binding profiles in the androgen-independent setting [13,17,18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported recently that DNA damage caused by ionizing radiation leads to the activation of AR, which in turn induces the expression of DNA repair genes that promote the survival of irradiated prostate cancer cells (47,48). Based on these reports, we expected that AR-inactivation would down regulate DDR signaling pathways and block the repair of damaged telomeres.…”
Section: Discussionmentioning
confidence: 94%
“…Men with >50% cores positive, perineural invasion, or cT2b-c disease had a superior 5-year biochemical control of 96% when treated with a brachytherapy boost compared to 87% when treated with dose-escalated external beam radiotherapy alone. As ADT also improves outcomes in patients that tend to have larger tumors (unfavorable risk patients), ADT may in fact also be acting as an alternative way to dose escalate -by sensitizing cancer cells to radiation (21).…”
Section: Resultsmentioning
confidence: 99%